Hyponatremic encephalopathy: An uncommon presentation associated with dengue shock syndrome: Two case reports - Hasmukh Chapsi Gala (Wolters Kluwer Medknow Publications, 2021)
Hyponatremia of mild-to-moderate degree is commonly seen in dengue infection. Severe hyponatremia with encephalopathy in dengue infection is rarely seen. Two cases of dengue shock syndrome presented with severe hyponatremia and hyponatremic encephalopathy. Following correction of hyponatremia, sensorium normalized in both cases. Serum sodium levels should be checked and monitored in patients of dengue fever, especially with altered sensorium, as early recognition and management of such hyponatremia can prevent serious morbidity and even mortality.